ANALYSIS OF TERM OF TRADE (TOT) FOR INDONESIA BAUXITE - HARTA HARYADI (Puslitbang tekMIRA, 2012)
Indonesia does not have a processing unit for bauxite. As a result all raw materials are exported. In contrast, the alumina is imported to fulfill the domestic need for aluminum industry. In terms of evaluating bauxite export, term of trade (TOT) analysis was conducted. Method used to calculate the TOT is carried out using net barter of TOT formula. The parameter include the export price compared to the import one. If the bauxite price increases and the import price decreases, the TOT is surplus. Contrarily, if the export price decreases and the import price increases, the TOT is deficit. To calculate the ratio of the export volume against the import volume used the grass barter of TOT. The measured parameter is the export volume compared to the import one. If the export volume increases and the import decreases, the TOT is surplus. On the other hand, if the export volume decreases and the import volume increases, the TOT is deficit. In 2003, the net barter of TOT was 0.07 and the grass barter of TOT was 87,874, but in 2010, the net barter of TOT was 0.09 and the grass barter of TOT was 5,809.53. Results of the TOT values indicate that Indonesia was still the exporter of bauxite raw material with an average of export value was lower than that of the import one, although its volume was significant due to the very low price. Indonesian bauxite export value will increase, if the processing unit immediately established